2018
DOI: 10.1016/j.jand.2017.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Alcoholic Beverage Consumption with Dietary Intake, Waist Circumference, and Body Mass Index in US Adults: National Health and Nutrition Examination Survey 2003-2012

Abstract: Differences in dietary intake across drinking subgroups and separation of former drinkers from nondrinkers should be considered in studies of alcohol intake in relation to WC and BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 43 publications
5
42
0
Order By: Relevance
“…The smallest WC in the low and moderate range of alcohol consumption identified in our study population was also found by others (Tolstrup et al, 2005). The below cut-off values of WC, even adjusted to the BMI, in men with moderate or excessive consumption might not be a positive finding, but a first sign of malnutrition associated with the onset of alcoholism (Butler et al, 2017, Tolstrup et al, 2005. Overall, our results are corresponding to the U shape relation that was found between alcohol intake, no matter what type (wine, beer or spirits) and metabolic components (Djoussee et al, 2004).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The smallest WC in the low and moderate range of alcohol consumption identified in our study population was also found by others (Tolstrup et al, 2005). The below cut-off values of WC, even adjusted to the BMI, in men with moderate or excessive consumption might not be a positive finding, but a first sign of malnutrition associated with the onset of alcoholism (Butler et al, 2017, Tolstrup et al, 2005. Overall, our results are corresponding to the U shape relation that was found between alcohol intake, no matter what type (wine, beer or spirits) and metabolic components (Djoussee et al, 2004).…”
Section: Resultssupporting
confidence: 82%
“…The influence was not reproduced in the high beer intake group, with lower, although non-significant WC than in the moderate consumption group. Less non-alcoholic energy food consumed by heavy drinkers was found by others (Butler et al, 2017). In line with these divergent results, a recent meta-analysis concluded that there is no scientific data consistently connecting the moderate beer ingestion with obesity, both general and abdominal (Bendsen et al, 2013).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…There is also limited evidence suggesting that gender modifies the association between weight status and alcohol use (Gearhardt and Corbin, ). For example, among women, the literature consistently suggests that there is an inverse relationship between alcohol use and BMI (Butler et al., ; Gearhardt and Corbin, ; Lahti‐Koski et al., ). However, in men, research has not shown a consistent direction in the relationship between alcohol use and BMI (Butler et al., ; Gearhardt and Corbin, ; Lahti‐Koski et al., ; Lean et al., ).…”
mentioning
confidence: 99%